2011
DOI: 10.1021/ja206279b
|View full text |Cite
|
Sign up to set email alerts
|

Lysine-Specific Molecular Tweezers Are Broad-Spectrum Inhibitors of Assembly and Toxicity of Amyloid Proteins

Abstract: Amyloidoses are diseases characterized by abnormal protein folding and self-assembly, for which no cure is available. Inhibition or modulation of abnormal protein self-assembly therefore is an attractive strategy for prevention and treatment of amyloidoses. We examined Lys-specific molecular tweezers and discovered a lead compound termed CLR01, which is capable of inhibiting the aggregation and toxicity of multiple amyloidogenic proteins by binding to Lys residues and disrupting hydrophobic and electrostatic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

37
474
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 266 publications
(513 citation statements)
references
References 58 publications
(106 reference statements)
37
474
2
Order By: Relevance
“…Previously, we showed that CLR01 bound to Aβ40 at distinct sites, Lys16, Lys28, and to a low extent Arg5, 16 consistent with its putative mechanism of action. Because EGCG showed similar or stronger inhibitory effects, we asked whether it bound to similar sites on Aβ.…”
Section: ■ Results and Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…Previously, we showed that CLR01 bound to Aβ40 at distinct sites, Lys16, Lys28, and to a low extent Arg5, 16 consistent with its putative mechanism of action. Because EGCG showed similar or stronger inhibitory effects, we asked whether it bound to similar sites on Aβ.…”
Section: ■ Results and Discussionsupporting
confidence: 72%
“…At low CLR01 concentrations, these changes occurred predominantly around the three cationic bindings sites, and as the concentration of CLR01 increased, gradually the entire spectrum was affected ( Figure 5B), likely due to Aβ selfassembly into nontoxic oligomers. 16 In contrast, only slight resonance perturbation was found in Aβ40:EGCG spectra at ratios up to 1:4 compared to Aβ40 alone ( Figure 5A and B). The resonances affected the most were in the regions Aβ(11− 15), Aβ(16−23), and Aβ(31−33), yet due to the low magnitude of the perturbation these data are difficult to interpret.…”
Section: ■ Results and Discussionmentioning
confidence: 84%
See 3 more Smart Citations